Somatization Mediates the Relationship Between Childhood Trauma and Pain Ratings in Patients with Irritable Bowel Syndrome - Schubach, Abigail; Quigley, Brian M; Lackner, Jeffrey M; Gudleski, Gregory D (Journal of clinical gastroenterology, 2024)
To identify potential mechanisms by which childhood trauma may lead to the adult development of abdominal symptoms in patients with irritable bowel syndrome (IBS). Patients with IBS frequently report a history of childhood trauma. The pathophysiology by which abdominal pain arises in patients with IBS is multidimensional, consisting of both peripheral factors, such as altered motility, inflammation, and bacterial overgrowth, as well as central factors, such as psychological distress and neuro-hormonal dysregulation. Adult psychological factors (anxiety, depression, and somatization) were examined to determine if they mediate the relationship between retrospective reports of childhood trauma and current adult IBS abdominal symptoms in a study of 436 patients (M age=41.6, 79% F) meeting Rome III diagnosis criteria. Childhood trauma was measured using retrospective questions assessing physical and sexual abuse. Psychological factors in adulthood were measured with the subscales of the Brief Symptom Inventory-18. Outcome variables included adult IBS symptoms of abdominal pain, bloating, and satisfaction with bowel habits from the IBS Symptoms Severity Scale. Results indicated that somatization mediated the relationship between childhood abuse and abdominal pain and bloating but not bowel satisfaction. This study provides insight into the multifactorial nature of IBS-associated abdominal pain in patients with a history of childhood trauma, elucidating the need for a trauma-informed treatment approach for patients with histories of abuse.